A textured insole improves gait symmetry in individuals with stroke. Issue 23 (6th November 2018) - Ma, Charlie C.; Rao, Noel; Muthukrishnan, Sriranjini; Aruin, Alexander S.
Abstract: Purpose: Gait asymmetry is a common consequence of stroke and improving gait symmetry is an important goal of rehabilitation. We investigated the effect of a single textured insole in improving gait symmetry in individuals with stroke. Method: Seventeen individuals with stroke who had asymmetrical gait were recruited and required to walk with a textured insole positioned in the shoe on the unaffected side or without the insole. Gait parameters were evaluated using the instrumented walkway. Gait velocity, cadence, and symmetry indices for the spatial and temporal parameters of gait and center of pressure displacements were obtained. Results: When walking with a textured insole, symmetry indexes for stance, single support phases of gait, as well as center of pressure displacements improved significantly. While using a textured insole, the duration of the stance phase and a single support phase decreased on the unaffected side and increased on the affected side significantly. Gait velocity and cadence were not affected by the use of the insole. Conclusions: Individuals with stroke walking with a textured insole placed in the shoe on the unaffected side improved the symmetry of their gait. The outcome provides a foundation for future investigations of the efficacy of using a single textured insole in gait rehabilitation of individuals with unilateral impairment. Implications for Rehabilitation: A single textured insole positioned in the shoe on the unaffected side improved gait symmetry in individuals with stroke. Gait velocity and cadence were not affected by the use of the insole.